Carboxymethyl cellulose acts as an interfacial binder to reinforce and stabilize anisotropic droplets in α-cyclodextrin pickering emulsions - Hiroyuki Kono; Risa Hashimoto; Suzuno Sato; Hibiki Yamashita; Baku Onishi; Koharu Sasa; Muneaki Tomotake; Shunsuke Nishio; Makoto Ogata (Food Hydrocolloids, 2026)

A new species of Priacanthus from the western Pacific Ocean, with a redescription of Priacanthus blochii Bleeker 1853 (Perciformes: Priacanthidae) - Shintaro Hashimoto; Hiroyuki Motomura (Ichthyological Research, 2026)

Analysis of dispersal characteristics of five food powders for avoiding unintentional food allergen cross-contact during food processing - Hiroyuki Hashimoto; Koichiro Ogata; Tatsuya M. Ikeda; Masato Yoshimitsu; Kyohei Kiyota (Journal of Food Engineering, 2026)

Elucidating the antioxidative mechanisms by blending rice bran oil with canola oil at ambient temperature - Shota Koishi; Sari Honda; Midori Matsuki; Kazue Sawada; Hiroyuki Hashimoto; Yuki Kadono; Halida Rahmania; Yurika Otoki; Shunji Kato; Kiyotaka Nakagawa (Food Research International, 2025)

A new species of bigeye, Priacanthus gracilis (Perciformes: Priacanthidae), from eastern Australia - Shintaro Hashimoto; Hiroyuki Motomura (Ichthyological Research, 2025)

Difference in Clinical Phenotype, Mutation Position, and Structural Change of RNF213 Rare Variants Between Pediatric and Adult Japanese Patients with Moyamoya Disease - Shunsuke Nomura; Hiroyuki Akagawa; Koji Yamaguchi; Kenko Azuma; Akikazu Nakamura; Atsushi Fukui; Fumiko Matsuzawa; Yasuo Aihara; Tatsuya Ishikawa; Yosuke Moteki; Kentaro Chiba; Kazutoshi Hashimoto; et al. (Translational Stroke Research, 2024)

Anti-biofouling performance and microbial communities of an integrated fixed-film activated sludge membrane bioreactor with a fibrous carrier material: Pilot-scale demonstration - Hiroyuki Yoshino; Hop Van Phan; Naomichi Mori; Naoki Ohkuma; Masaki Kawakami; Masahiko Nihei; Satoshi Hashimoto; Ken Wakabayashi; Tomoyuki Hori; Akihiko Terada (Science of The Total Environment, 2024)

Evaluation of the risk of diarrhea induced by epidermal growth factor receptor tyrosine kinase inhibitors with cultured intestinal stem cells originated from crypts in humans and monkeys - Yoshiki Hashimoto; Kazuya Maeda; Osamu Shimomura; Yoshihiro Miyazaki; Shinji Hashimoto; Akiko Moriyama; Tatsuya Oda; Hiroyuki Kusuhara (Toxicology in Vitro, 2023)

Strategic roadmap to assess forest vulnerability under air pollution and climate change - Alessandra De Marco; Pierre Sicard; Zhaozhong Feng; Evgenios Agathokleous; Rocio Alonso; Valda Araminiene; Algirdas Augustatis; Ovidiu Badea; James C. Beasley; Cristina Branquinho; Viktor J. Bruckman; Alessio Collalti; et al. (Global Change Biology, 2022)
Although it is an integral part of global change, most of the research addressing the effects of climate change on forests have overlooked the role of environmental pollution. Similarly, most studies investigating the effects of air pollutants on forests have generally neglected the impacts of climate change. We review the current knowledge on combined air pollution and climate change effects on global forest ecosystems and identify several key research priorities as a roadmap for the future. Specifically, we recommend (1) the establishment of much denser array of monitoring sites, particularly in the South Hemisphere; (2) further integration of ground and satellite monitoring; (3) generation of flux‐based standards and critical levels taking into account the sensitivity of dominant forest tree species; (4) long‐term monitoring of N, S, P cycles and base cations deposition together at global scale; (5) intensification of experimental studies, addressing the combined effects of different abiotic factors on forests by assuring a better representation of taxonomic and functional diversity across the ~73,000 tree species on Earth; (6) more experimental focus on phenomics and genomics; (7) improved knowledge on key processes regulating the dynamics of radionuclides in forest systems; and (8) development of models integrating air pollution and climate change data from long‐term monitoring programs.

Leishmanicidal phenolic compounds derived from Dalbergia cultrata - Kanami Mori-Yasumoto; Yukihiro Hashimoto; Yutaka Agatsuma; Hiroyuki Fuchino; Ko Yasumoto; Osamu Shirota; Motoyoshi Satake; Setsuko Sekita (Natural Product Research, 2021)

Clinical features, pathogenesis, and management of stroke-like episodes due to MELAS - Syuichi Tetsuka; Tomoko Ogawa; Ritsuo Hashimoto; Hiroyuki Kato (Metabolic Brain Disease, 2021)

Prevalence of antibodies against human respiratory viruses potentially involving anthropozoonoses in wild bonobos - Tomoyuki Yoshida; Hiroyuki Takemoto; Tetsuya Sakamaki; Nahoko Tokuyama; John Hart; Terese Hart; Jef Dupain; Amy Cobden; Mbangi Mulavwa; Chie Hashimoto; Mina Isaji; Akihisa Kaneko; et al. (Primates, 2021)

Detection and Determination of Fumonisins B1, B2, and B3 Contaminating Japanese Domestic Wine by Liquid Chromatography Coupled to Tandem Mass Spectrometry (LC–MS/MS) - Hiroyuki Nakagawa; Ruiko Hashimoto; Yosuke Matsuo; Yuki Sago; Koji Yokoyama; Haruo Takahashi (Current Microbiology, 2020)

Ruptured de novo posterior inferior cerebellar artery aneurysm associated with fibromuscular dysplasia - Hiroshi Yokota; Takahide Yaegaki; Kaoru Horiuchi; Kenta Fujimoto; Hiroyuki Hashimoto (Acta Neurologica Belgica, 2020)

Intergroup Encounters of Chimpanzees (Pan troglodytes) from the Female Perspective - Chie Hashimoto; Mina Isaji; Keiko Mouri; Hiroyuki Takemoto (International Journal of Primatology, 2020)

Melanogenesis inhibitory activity of components from Salam leaf (Syzygium polyanthum) extract - Andriyana Setyawati; Kae Hirabayashi; Kosei Yamauchi; Hiroyuki Hattori; Tohru Mitsunaga; Irmanida Batubara; Rudi Heryanto; Hiroshi Hashimoto; Mitsuyuki Hotta (Journal of Natural Medicines, 2018)

Establishment of oct4:egfp transgenic and oct4:egfp /β-actin:DsRed double transgenic medaka lines - Shinpei Yokota; Rinta Matsuno; Hiroyuki Kato; Hisashi Hashimoto; Masato Kinoshita; Hayato Yokoi; Tohru Suzuki (In Vitro Cellular & Developmental Biology - Animal, 2016)

Differential effects of docoosahexaenoic and arachidonic acid on fatty acid composition and myosin heavy chain-related genes of slow- and fast-twitch skeletal muscle tissues - Michio Hashimoto; Takayuki Inoue; Masanori Katakura; Shahdat Hossain; Abdullah Al Mamun; Kentaro Matsuzaki; Hiroyuki Arai; Osamu Shido (Molecular and Cellular Biochemistry, 2016)

Apollon/Bruce is upregulated by Humanin - Yuichi Hashimoto; Yuji Takeshita; Mikihiko Naito; Hiroyuki Uchino; Masaaki Matsuoka (Molecular and Cellular Biochemistry, 2014)

Human proximity and habitat fragmentation are key drivers of the rangewide bonobo distribution - Jena R. Hickey; Janet Nackoney; Nathan P. Nibbelink; Stephen Blake; Aime Bonyenge; Sally Coxe; Jef Dupain; Maurice Emetshu; Takeshi Furuichi; Falk Grossmann; Patrick Guislain; John Hart; et al. (Biodiversity and Conservation, 2013)

Effect of feeding rotifers enriched with taurine on the growth and survival of larval amberjack Seriola dumerili - Hiroyuki Matsunari; Hiroshi Hashimoto; Takashi Iwasaki; Kentaro Oda; Yoshitsugu Masuda; Hitoshi Imaizumi; Kazuhisa Teruya; Hirofumi Furuita; Takeshi Yamamoto; Kazuhisa Hamada; Keiichi Mushiake (Fisheries Science, 2013)

Changes in mineral concentrations in amberjack Seriola dumerili larvae during seed production: high concentrations of certain minerals in rotifers do not directly affect the mineral concentrations in larvae - Takeshi Yamamoto; Hiroyuki Matsunari; Takashi Iwasaki; Hiroshi Hashimoto; Isao Kai; Hiroto Hokazono; Kazuhisa Hamada; Kazuhisa Teruya; Takashi Hara; Hirofumi Furuita; Keiichi Mushiake (Fisheries Science, 2013)

Effect of different algae used for enrichment of rotifers on growth, survival, and swim bladder inflation of larval amberjack Seriola dumerili - Hiroyuki Matsunari; Hiroshi Hashimoto; Kentaro Oda; Yoshitsugu Masuda; Hitoshi Imaizumi; Kazuhisa Teruya; Hirofumi Furuita; Takeshi Yamamoto; Kazuhisa Hamada; Keiichi Mushiake (Aquaculture International, 2012)

Neural Stem Cells and New Neurons in the Cerebral Cortex of Stroke-Prone Spontaneously Hypertensive Rats After Stroke - Tatsuki Itoh; Takao Satou; Kumiko Takemori; Shigeo Hashimoto; Hiroyuki Ito (Journal of Molecular Neuroscience, 2010)

The Novel Free Radical Scavenger, Edaravone, Increases Neural Stem Cell Number Around the Area of Damage Following Rat Traumatic Brain Injury - Tatsuki Itoh; Takao Satou; Shozo Nishida; Masahiro Tsubaki; Shigeo Hashimoto; Hiroyuki Ito (Neurotoxicity Research, 2009)

Nutritional evaluation of rotifers in rearing tanks without water exchange during seed production of amberjack Seriola dumerili - Takeshi Yamamoto; Kazuhisa Teruya; Takashi Hara; Hiroto Hokazono; Isao Kai; Hiroshi Hashimoto; Hirofumi Furuita; Hiroyuki Matsunari; Keiichi Mushiake (Fisheries Science, 2009)

Improvement of cerebral function by anti-amyloid precursor protein antibody infusion after traumatic brain injury in rats - Tatsuki Itoh; Takao Satou; Shozo Nishida; Masahiro Tsubaki; Shigeo Hashimoto; Hiroyuki Ito (Molecular and Cellular Biochemistry, 2009)

Nutritional evaluation of live food organisms and commercial dry feeds used for seed production of amberjack Seriola dumerili - Takeshi YAMAMOTO; Kazuhisa TERUYA; Takashi HARA; Hiroto HOKAZONO; Hiroshi HASHIMOTO; Nobuhiro SUZUKI; Yasuro IWASHITA; Hiroyuki MATSUNARI; Hirofumi FURUITA; Keiichi MUSHIAKE (Fisheries Science, 2008)

Gene Transfer by DNA/mannosylated Chitosan Complexes into Mouse Peritoneal Macrophages - Mayu Hashimoto; Minoru Morimoto; Hiroyuki Saimoto; Yoshihiro Shigemasa; Hironobu Yanagie; Masazumi Eriguchi; Toshinori Sato (Biotechnology Letters, 2006)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

A novel glucosyltransferase involved in steroid saponin biosynthesis in Solanum aculeatissimum - Atsuko Kohara; Chiharu Nakajima; Kimiko Hashimoto; Toshihiko Ikenaga; Hiroyuki Tanaka; Yukihiro Shoyama; Shigeo Yoshida; Toshiya Muranaka (Plant Molecular Biology, 2005)

Establishment and Characterization of Two Squamous Cell Carcinoma Cell lines (HYVC and HMVC) Derived from Vulva - Kazushige KIGUCHI; Isamu ISHIWATA; Chieko ISHIWATA; Masanori IWATA; Bunpei ISHIZUKA; Hiroyuki YOSHIKAWA; Toshiaki TACHIBANA; Hisashi HASHIMOTO; Hiroshi ISHIKAWA (Human Cell, 2002)

Establishment and Characterization of a Lymphoepithelial-like Carcinoma Cell Line (HUUCLEC) Derived from the Human Uterine Cervix. - Kazushige KIGUCHI; Isamu ISHIWATA; Yuko TOKIEDA; Megumi IGUCHI; Chieko ISHIWATA; Masanori IWATA; Bunpei ISHIZUKA; Hiroyuki YOSHIKAWA; Toshiaki TACHIBANA; Hisashi HASHIMOTO; Hiroshi ISHIKAWA (Human Cell, 2002)

Cell proliferation and death of Hertwig's epithelial root sheath in the rat - Hiroyuki Kaneko; Sadamitsu Hashimoto; Yasunobu Enokiya; Hideki Ogiuchi; Masaki Shimono (Cell and Tissue Research, 1999)

Transposon tagging in rice - Takeshi Izawa; Tohru Ohnishi; Toshitsugu Nakano; Nobuhiro Ishida; Hiroyuki Enoki; Hisako Hashimoto; Kimiko Itoh; Rie Terada; Chuanyn Wu; Chikara Miyazaki; Tomoko Endo; Shigeru Iida; et al. (Plant Molecular Biology, 1997)